Promoting Islamic Charitable Donations: Insights from Palembang - Pranata, Eka Octavian; Sajjad, M; Azra, Uliya; Nabila Fadhilah (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2025)
This research investigates the impact of influencer marketing and electronic word-of-mouth (eWOM) on Islamic charitable donations in Palembang, Indonesia. Highlighting the significance of zakat, infaq, waqf, and sadaqah, the study employs qualitative methods, including interviews and social media analysis. Findings reveal that authentic influencers enhance trust and drive donor engagement, while eWOM amplifies campaign reach through shared experiences. However, challenges like commercialization and the need for influencer accountability are identified. This research underscores the potential of digital strategies to align with Islamic charitable principles, offering insights for future research and practical applications in promoting Islamic charity.